2005
DOI: 10.2989/16085900509490349
|View full text |Cite
|
Sign up to set email alerts
|

The impact of participatory and non-participatory evaluations on meeting project objectives

Abstract: This study investigates the value of participation on meeting a project's objectives by comparing the impact of participatory and non-participatory evaluation frameworks. We assessed HIV/AIDS projects that shared similarities in terms of objectives and implementation strategies, but differed in their evaluation strategies, in order to identify differences in the outcome of the projects on the beneficiaries. The study concentrated on documentary and interview evidence of communication-based HIV/AIDS projects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Creating broad ownership of research through public involvement seems to be particularly important in projects that aim to increase people's knowledge and awareness and/or change their attitudes and behaviour. For example, a study of different approaches to developing health promotion programmes, showed that these projects are more likely to lead to change if the public are involved in the development, implementation and evaluation stages (Niba & Green 2005).…”
Section: Case Study 35mentioning
confidence: 99%
“…Creating broad ownership of research through public involvement seems to be particularly important in projects that aim to increase people's knowledge and awareness and/or change their attitudes and behaviour. For example, a study of different approaches to developing health promotion programmes, showed that these projects are more likely to lead to change if the public are involved in the development, implementation and evaluation stages (Niba & Green 2005).…”
Section: Case Study 35mentioning
confidence: 99%
“…In their work they discuss how using photography as a medium for group work, resulted in participants having an increased sense of control over their own lives as well as becoming community change agents through empowering them as experts in their own lives. Based in South Africa, Niba and Green (2005) compare participatory and non-participatory frameworks for evaluation in HIV/AIDS projects and conclude that participatory frameworks create an enabling environment to meet objectives, in particular, improved group awareness, knowledge and attitudes, as well as internalisation of objectives. More recently, international studies have identified improved public participation, sustainability and better multi-disciplinary working as positive outcomes from participatory approaches in community evaluation activities (Edwards and Roelofs, 2006;Speilman et al, 2006;White 2006).…”
Section: Introductionmentioning
confidence: 99%